Linguistic and Teaching Competence in the FL Classroom - Mardešić, Sandra (Array, 2013)
Over the last fifteen years a number of studies in foreign language teaching education has increased and resulted in defining foreign language teaching competencies that should be developed through teacher education (European Profile for Language Teacher Education, 2004). Since previous studies have indicated that student teachers and practicing teachers differ in their evaluation of the importance of some categories of FL teaching competencies, the aim of this study was to investigate differences between student teachers and practicing teachers evaluation of the successfulness of a FL lesson. In the first part of the study 66 student teachers of English, French and Italian evaluated the successfulness of their own lessons using the check list by which their teachers or mentors graded their performance. Our results also indicate that students and practicing teachers evaluations differed. While the mentors seemed to focus on the level of linguistic competence and elements related to it, as well as the choice and implementation of different teaching methods, the student teachers seemed to focus more on the quality of interaction, choice of teaching materials and the planning of the lesson. The second part of the study included a larger sample of both teachers and student teachers, and examined their attitudes towards the importance of certain teaching competencies in the classroom. The results indicate that the evaluation categories need to be discussed and agreed on between teachers and student teachers at the beginning of the practical part of teacher education.